Biomaterials for treating sepsis-induced thromboinflammation - Lutz, Halle; Brown, Ashley C. (Frontiers in Biomaterials Science, 2023)
Sepsis is a common and life-threatening disorder with an alarmingly high mortality rate. Unfortunately, this rate has not decreased significantly over the last decade and the number of septic cases is increasing each year. Despite sepsis affecting millions of people annually, there is still not an established standard of care. The development of a therapy that targets the thromboinflammation characteristic of sepsis is imperative. Until recently, research has focused on uncovering individual pathways to target. As more of the pathophysiology of sepsis has become understood and more biomarkers uncovered, the interplay between endothelial cells, platelets, and leukocytes has emerged as a critical event. Therefore, a multi-targeted approach is clearly required for designing an effective treatment for sepsis. The versatility of biomaterials offers a promising solution in that they can be designed to target and affect multiple pathways and systems and safely inhibit excessive inflammation while maintaining hemostasis. Already, studies have demonstrated the ability of biomaterials to target different processes and stages in sepsis-induced inflammation and coagulopathy. Moreover, some biomaterials offer inherent anti-inflammatory and hemostatic qualities. This review aims to discuss the most recent advancements in biomaterial development designed to address inflammation, coagulopathy, and thromboinflammation.